2019
DOI: 10.3390/nu11102507
|View full text |Cite
|
Sign up to set email alerts
|

Translation of a Mediterranean-Style Diet into the Australian Dietary Guidelines: A Nutritional, Ecological and Environmental Perspective

Abstract: A Mediterranean diet (MedDiet) has been widely investigated and promoted as one of the ‘healthiest’ dietary patterns with respect to reductions in chronic disease risk and longevity. Moreover, it also emphasizes a plant-based dietary pattern consistent with an environmentally sustainable healthy reference diet conveyed by the EAT-Lancet Commission report. Nevertheless, the MedDiet does not exclude, but rather moderates consumption of animal-based foods, and therefore has emerged as a dietary pattern that could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 77 publications
0
24
0
Order By: Relevance
“…The detailed analysis of the water footprint showed that adaptation to the planetary healthy diet could be the most advantageous among the analyzed scenarios since it has the best synergistically characteristic features regarding both health and sustainability. Thus, Hungary could follow the footsteps of those countries that have included sustainability in their dietary guidelines [5,8,26,27]. The further investigations in the field should be devoted to development of research of links between diet nutrition and quality of life, particularly poverty, and overall well-being as one of the key features of sustainable development, defined in [60][61][62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed analysis of the water footprint showed that adaptation to the planetary healthy diet could be the most advantageous among the analyzed scenarios since it has the best synergistically characteristic features regarding both health and sustainability. Thus, Hungary could follow the footsteps of those countries that have included sustainability in their dietary guidelines [5,8,26,27]. The further investigations in the field should be devoted to development of research of links between diet nutrition and quality of life, particularly poverty, and overall well-being as one of the key features of sustainable development, defined in [60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…Our aim was to make an integrated and specific assessment of the association of food consumption, dietary quality, and water footprint. The recent trend in studies on sustainable nutrition is directed toward an urgent change in the dietary recommendation that respects the environment, as has already been carried out by the most advanced countries [ 7 , 8 , 26 , 27 ] and as is recommended by the Food and Agriculture Organization of the United Nations (FAO). The aim of the current study was to analyze the consequences of the current, and some recommended, dietary patterns on the water footprint, applying a small, lesser-known Central European, landlocked country, Hungary, as a value-added for a comparison of the environmental effects of different diets.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed above, the benefits of MedDiet consumption have been well studied in Mediterranean countries and evaluated in cohorts from Northern Europe [ 31 ], US [ 32 ], and Australia [ 33 ]. However, until now, similar studies do not exist in Latin America.…”
Section: Mediterranean-type Ecosystem Of Central Chile and Local Imentioning
confidence: 99%
“…In Chile, over 82% of 400 surveyed people reported that cooking is a pleasure for them, most of them cook with a companion, which contributes to social continuity, and they favor (70%) Chilean gastronomy [ 113 ]. Interestingly, the MedDiet has already been translated into specific culturally adapted food and preparations in other countries [ 33 ]. Chile strongly fits in this dietary pattern within its traditional dishes.…”
Section: Sustainability Of the Mediterranean Dietmentioning
confidence: 99%
“…In order to translate the MedDiet to a multiethnic population, for example in Australia, there is a need for a consistent definition of the MedDiet to ensure the key elements are captured and translated so that the translated MedDiet model retains authenticity [21] . Translating the MedDiet to non-Mediterranean populations with different cultural food habits and cultural customs has been discussed as rather challenging [22] .…”
Section: Cancer Riskmentioning
confidence: 99%